Equity in health insurance schemes enrollment in low and middle-income countries: A systematic review and meta-analysis - Doris Osei Afriyie; Blerina Krasniq; Brady Hooley; Fabrizio Tediosi; Günther Fink (BMC, 2022)
Abstract Background Ensuring access to essential quality health services and reducing financial hardship for all individuals regardless of their ability to pay are the main goals of universal health coverage. Various health insurance schemes have been recently implemented in low- and middle-income countries (LMICs) to achieve both of these objectives. We systematically reviewed all available literature to assess the extent to which current health insurance schemes truly reach the poor and underserved populations in LMICs. Methods In the systematic review, we searched on PubMed, Web of Science, EconLit and Google Scholar to identify eligible studies which captured health insurance enrollment information in LMICs from 2010 up to September 2019. Two authors independently selected studies, extracted data, and appraised included studies. The primary outcome of interest was health insurance enrollment of the most vulnerable populations relative to enrollment of the best-off subgroups. We classified households both with respect to their highest educational attainment and their relative wealth and used random-effects meta-analysis to estimate average enrollment gaps. Results 48 studies from 17 countries met the inclusion criteria. The average enrollment rate into health insurance schemes for vulnerable populations was 36% with an inter-quartile range of 26%. On average, across countries, households from the wealthiest subgroup had 61% higher odds (95% CI: 1.49 to 1.73) of insurance enrollment than households in the poorest group in the same country. Similarly, the most educated groups had 64% (95% CI: 1.32 to 1.95) higher odds of enrollment than the least educated groups. Conclusion The results of this study show that despite major efforts by governments, health insurance schemes in low-and middle-income countries are generally not reaching the targeted underserved populations and predominantly supporting better-off population groups. Current health insurance designs should be carefully scrutinized, and the extent to which health insurance can be used to support the most vulnerable populations carefully re-assessed by countries, which are aiming to use health insurance schemes as means to reach their UHC goals. Furthermore, studies exploring best practices to include vulnerable groups in health insurance schemes are needed. Registration Not available